Yesss! : the S.U.M.O. secrets to being a positive, confident teenager - McGee, Paul, 1964-; Osborne, Fiona (United Kingdom : John Wiley, 2021)
"Since the publication of Paul McGee's best-selling book Shut Up, Move On SUMO, the SUMO principles have helped thousands of people around the world to build the resilience, confidence and motivation to cope with life's challenges, and be the best they can be. Under its alternative name of Stop, Understand, Move On, YESSS! The SUMO secrets to being a positive, confident teenager helps young people and the professionals who work with them to get more out of themselves, get more out of others and get more out of life! Using the same SUMO principles as the original book, this new edition for young people will help them learn resilience, greater awareness of their feelings and emotions, and raise their aspirations. In other words, a set of skills for life. This book will teach you: To take responsibility for your life, and to own and understand your feelings. To change your mindset, and why our mindset matters That it's OK not to be OK!. To have aspirations, set goals and dare to dream"--
Includes index.
Keywords: Self-actualization (Psychology); Self-confidence in adolescence